GEMINGA: NEW OBSERVATIONS AT LOW RADIO FREQUENCIES - Malofeev, V. M.; Malov, O. I.; Logvinenko, S. V.; Teplykh, D. A. (Одеські астрономічні публікації, 2012)
After nearly 10 years, we have succeeded to detect radio emission from Geminga more again. In this report we present new evidence for presence of radio emission from Geminga in the range 42-112 MHz. The observations were carried out on two sensitive transit radio telescopes We used three new digital receivers to detect the pulses and to obtain dynamic spectra.The examples of mean pulse profiles are presented. Exact value of the dispersion measure have been calculated using the simultaneous observations at three frequencies.